Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1038/modpathol.3800018
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the hMLH1 promoter with absent hMLH1 expression in medullary-type poorly differentiated colorectal adenocarcinoma in the elderly

Abstract: To clarify the significance of hMLH1 promoter hypermethylation in the development of medullary-type poorly differentiated colorectal adenocarcinoma, we studied the status of promoter methylation and hMLH1 expression in 23 medullary-type and 12 pleomorphic-type carcinomas, as well as the pathology and microsatellite status. In medullary-type carcinomas, the percentages of cases with promoter methylation (83%) and an absence of hMLH1 expression (91%) were significantly higher than in pleomorphic-type carcinomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 27 publications
(41 reference statements)
9
62
0
Order By: Relevance
“…Several reports, together with our results, have demonstrated that microsatellite-unstable gastric carcinomas are significantly associated with the elderly [2,[4][5][6], women [3,5], and antral location [2,4,5,9]. These characteristics are similar to those of medullary-type, poorly differentiated adenocarcinoma of the colorectum, which is a representative MSI-positive carcinoma showing predominant occurrence in older age, women, and the proximal colon [26]. Medullary-type colorectal carcinoma shows hypermethylation of the hMLH1 promoter with loss of hMLH1 expression [26].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Several reports, together with our results, have demonstrated that microsatellite-unstable gastric carcinomas are significantly associated with the elderly [2,[4][5][6], women [3,5], and antral location [2,4,5,9]. These characteristics are similar to those of medullary-type, poorly differentiated adenocarcinoma of the colorectum, which is a representative MSI-positive carcinoma showing predominant occurrence in older age, women, and the proximal colon [26]. Medullary-type colorectal carcinoma shows hypermethylation of the hMLH1 promoter with loss of hMLH1 expression [26].…”
Section: Discussionsupporting
confidence: 68%
“…These characteristics are similar to those of medullary-type, poorly differentiated adenocarcinoma of the colorectum, which is a representative MSI-positive carcinoma showing predominant occurrence in older age, women, and the proximal colon [26]. Medullary-type colorectal carcinoma shows hypermethylation of the hMLH1 promoter with loss of hMLH1 expression [26]. As already mentioned, papillary adenocarcinoma of the stomach has the same features [8].…”
Section: Discussionsupporting
confidence: 53%
“…4 An additional 10-20% of sporadic colorectal carcinomas are associated with MSI 4 and these are virtually all associated with loss of hMLH1 protein expression, primarily due to methylation of the hMLH1 promoter. [4][5][6] Conversely, defective hMSH2 or hMSH6 is almost always due to germline mutations. 7 Several investigators have reported that colorectal carcinomas with defective MMR often show distinctive clinicopathologic features including location in the proximal colon, younger patient age, mucinous differentiation, and a host-immune response characterized by a Crohn's-like lymphoid reaction or tumor infiltrating lymphocytes.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] The World Health Organization recognizes MC as a separate entity of colorectal carcinoma in the 2010 edition of WHO Classification of Tumours of the Digestive System. 7 Medullary carcinoma typically presents as a large-sized tumor of the right side of the colon, especially in the cecum, in elderly patients, and is more frequently seen in women than in men, with a ratio of 2:1.…”
mentioning
confidence: 99%